EXPANSION OF MAQASID THOUGHT BEYOND MAQASID AL-SHARIAH: MAQASID AL-QURAN AS A NEW PARADIGM - Tazul Islam (Hamdard Islamicus, 2022)
The objective of this study is to examine a potential conceptual expansion of the concept of Maqasid (essential purposes of Islam). The contemporary developments in the Maqasid al-Shariah, a popular goal theory of Islam, remains largely unchanged from the theoretical point of view, which was developed by the traditional Muslim scholars. Although the implementation of Maqasid al-Shariah has significantly grown, its theoretical development remains limited. Some current Maqasid thinkers, however, are prompted to make efforts to broaden this goal notion. They have entitled this new endeavor as ‘Maqasid al-Quran’ instead of Maqasid al-Shariah to imply a more expansive interpretation of Maqasid. They argue that the journey of Maqasid al-Shariah should continue until it achieves a larger paradigm which might give it a wider methodological ability to function outside of the Maqasid al-Shariah framework. The researcher has used library data in the form of text from the pertinent books and scholarly articles to analyze new theoretical prospects of Maqasid. This study discovers that, in contrast to Maqasid al-Shariah which primarily focuses on the normative aspect of Islam, Maqasid al-Quran has the potential to be a broad Islamic goal theory since it expresses the goals of the entire Islamic discourse irrespective of normative aspect. It was defined more broadly than Maqasid al-Shariah by traditional and modern Maqasid scholars. Moreover, its methodological scope is deemed broader than that of Maqasid al- Shariah.